2005
DOI: 10.1074/jbc.m410000200
|View full text |Cite
|
Sign up to set email alerts
|

Polyunsaturated Fatty Acids Block Dendritic Cell Activation and Function Independently of NF-κB Activation

Abstract: Polyunsaturated fatty acids (PUFAs) modulate immune responses leading to clinically significant beneficial effects in a variety of inflammatory disorders. PUFA effects on T cells have been extensively studied, but their influence on human dendritic cells (DCs), which are the most potent antigen-presenting cells and play a key role in initiating immune responses, has not been elucidated so far. Here we show that PUFAs of the n-3 and n-6 series (arachidonic and eicosapentaenoic acid) affect human monocyte-derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
113
2
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(133 citation statements)
references
References 65 publications
15
113
2
3
Order By: Relevance
“…6 ) were not entirely in agreement with some in vitro studies showing that DHA suppressed LPS activation of macrophages and dendritic cells (43)(44)(45). This could be due to aforementioned differences (e.g., cell type, diet vs. in vitro treatment, etc.).…”
Section: Disruption Of Rafts With Fo Was Accompanied By Differential supporting
confidence: 58%
“…6 ) were not entirely in agreement with some in vitro studies showing that DHA suppressed LPS activation of macrophages and dendritic cells (43)(44)(45). This could be due to aforementioned differences (e.g., cell type, diet vs. in vitro treatment, etc.).…”
Section: Disruption Of Rafts With Fo Was Accompanied By Differential supporting
confidence: 58%
“…The rapid improvement in the n-6/n-3 ratio points to the possibility that n-3 PUFAs could be used as nutraceuticals to modify composition and organization to selectively initiate a change in cellular function with a high dose of PUFAs for a short time period. Based on data presented here and elsewhere, the most plausible splenic targets that respond to a change in membrane composition to suppress cellular function are CD4 + T cells and possibly DCs ( 13,15,37,38 ). The data from this study allow us to propose that n-3 PUFA inhibition of lymphocyte activation is not universal.…”
Section: Discussionmentioning
confidence: 77%
“…On the other hand, the maturation and antigen-presentation ability of dendritic cells can be inhibited by statins (80), the cholesterol-lowering class of drugs that has been found to have a number of immunomodulatory effects as well. Dendritic cells treated with polyunsaturated fatty acids of the n-3 and n-6 family also display a maturation block when challenged with lipopolysaccharide, suggesting that part of the reported anti-inflammatory and atheroprotective effect of these dietary fatty acids (81,82) may be linked to preventing dendritic cell activation (83). Finally, recent studies have identified other lipid mediators that may be responsible for retaining dendritic cells in the atherosclerotic plaque, namely PAF and 18:1 lysophosphatidic acid (84,85).…”
Section: Dendritic Cellsmentioning
confidence: 99%